بونیادی وێنەی كاریكاتێری لە پەندە شیعرییەكانی پیرەمێرددا (توێژینەوەی هەڵێنجراو) - كاكی, حەمەنوری عومەر; علی, صدیق اورحمان (Sulaimani Journal for Humanities, 2023)
Proverbs are product of each society's thoughts, views and efficiencies on phenomena and events and their worldview for the future, which have appeared as a result of the experiences of enlightened people, and the whole of society has participated in expressing and formulating them. Among them, the poetic proverbs which are the work of experienced and wise persons afterwards became the property of society which have an important value for any subject and purpose that we want to know the people's opinion about, especially their artistic form which is the main purpose of the study. In the view of importance of poetic proverbs and their artistic structure, construction of the caricatural imagery in private, this study investigates Piramerd’s poetic proverbs entitled (structure of the caricatural imagery in Piramerd’s Poetic Proverbs). The study looks for the construction of caricatural forms and identifies those characters are described in the caricatures of the poetry contents to reveal specific purpose. Besides, proverb teller wants people have sense of humor, he criticizes bad phenomena strongly in his society and he shows his messages to convert them. The study consists of two sections: the first section includes the concept of proverb, poetic proverb, and structure of the proverb caricatural imageries. In the second section, on the basis of the caricature characters, caricatures are classified, in all of them, human is appeared like center of the images, their only purpose is to criticize bad phenomena and change them. In this regard, the skills and efficiency of the proverb teller are fully reflected, and finally the results are showed.
Keywords: Proverbs; Piramerds Poetic Proverbs; caricatural imagery; caricatural proverbs